Body-worn cameras: a useful tool for police incident reconstruction. (8th April 2020) - Desmoulin, Geoffrey Thor; Nolette, Marc-André
Body-worn cameras are a tool commonly used in many police departments as a way to protect the officers and the public. However, their value has sometimes been questioned. A recent case, presented here, exemplifies the way body-cam footage can be used. Using the footage in conjunction with an injury biomechanics investigation process, it was possible to show that the officers involved delivered submaximal blows in order to control the suspect rather than aiming to deliberately harm the suspect. It was also shown that the duration of the baton intervention was reasonable as the time the officer took to change his response was within the limits presented in literature.